A method for estimating vaccine-preventable pediatric influenza pneumonia hospitalizations in developing countries: Thailand as a case study - Dawood, Fatimah S.; Fry, Alicia M.; Muangchana, Charung; Sanasuttipun, Wiwan; Baggett, Henry C.; Chunsuttiwat, Supamit; Maloney, Susan A.; Simmerman, James Mark (Vaccine, 2011)
The burden of influenza in children is increasingly appreciated; some middle-income countries are considering support for influenza vaccine programs. To support decision-making, methods to estimate the potential impact of proposed programs are needed. Using Thailand as a case-study, we present a model that uses surveillance data, published vaccine effectiveness estimates, and vaccination coverage assumptions to estimate the impact of influenza vaccination on pediatric influenza pneumonia hospitalizations. Approximately 56,000 influenza pneumonia hospitalizations occur annually among children aged <18 years in Thailand; 23,700 (41%) may be vaccine-preventable. Vaccination of 85% of Thai children aged 7 months–4 years might prevent 30% of all pediatric influenza pneumonia hospitalizations in Thailand.